Kairos and Telos in the 2024 U.S. Presidential Candidates’ Debate: Timing and Purpose - Rizky Munte; Jubilezer Sihite; Rony Arahta Sembiring (JELITA, 2025)
This research aimed to analyze the rhetorical strategies used in the 2024 U.S. presidential candidates’ debates between former President Donald Trump and Vice President Kamala Harris, with a particular focus on kairos and telos as types of rhetorical strategies. Additionally, the study calculated the most dominant types of rhetorical strategies employed by each candidate to justify their ideas and persuade voters about their electoral campaigns. The research subjects were the debates between the two candidates, focusing on their use of kairos (timing, social norms, and opportunity) and telos (purpose) as rhetorical devices. Donald Trump consisted timing (18), social norm (12), and opportunity (6), while Kalama Harris consisted timing (9), social norm (7), and opportunity (7). The results showed that both candidates used these rhetorical devices to deliver their ideas effectively at the right moment and with a clear purpose, enhancing their ability to persuade voters and increase their chances of winning the election.